2010
DOI: 10.1016/j.atmosres.2009.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging of aerosol particles by rain in a cloud resolving model

Abstract: We describe a below-cloud scavenging module of aerosol particles by raindrops for use in a three-dimensional mesoscale cloud resolving model. The rate of particle removal is computed by integrating the scavenging efficiency circulations to redistribute layers of aerosol particles in order to improve estimates of particle removal by below-cloud scavenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…For very small and very large particles, there is prevalently an agreement with theoretical studies [19,25,38]. However, theoretical parameterizations prevalently underestimate observed  values by one to two orders of magnitude for particles in the 0.1 μm -1 μm radius range and by one order of magnitude for particles smaller than 0.1 m, compared to the available field measurements [79].…”
Section: Below-cloud Scavengingsupporting
confidence: 66%
See 2 more Smart Citations
“…For very small and very large particles, there is prevalently an agreement with theoretical studies [19,25,38]. However, theoretical parameterizations prevalently underestimate observed  values by one to two orders of magnitude for particles in the 0.1 μm -1 μm radius range and by one order of magnitude for particles smaller than 0.1 m, compared to the available field measurements [79].…”
Section: Below-cloud Scavengingsupporting
confidence: 66%
“…Thus, there is a minimum collection efficiency for particles in the approximate range of 0.1 μm -1 μm, where phoretic and electric effects are felt [14,15,25,[35][36][37][38]. The exact depth, width and position of this minimum depend on the properties of the aerosols and hydrometeors, and on ambient conditions.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified version of the CMAQ model can distinguish between rainout and washout processes and ignores the washout process for accumulation-mode aerosols because particles of this size are much less efficiently removed by the collision of precipitating raindrops below clouds [Seinfeld and Pandis, 2006]. Several previous studies have shown that below-cloud scavenging is negligible for accumulation-mode aerosol particles when compared with in-cloud scavenging rates for low and moderate rainfall rates (0.1-10 mm h À1 ) [e.g., Andronache, 2003;Henzing et al, 2006;Berthet et al, 2010], supporting our treatment of the wet deposition process. While the CMAQ model explicitly treats aerosol microphysics, such as condensation and coagulation (i.e., aging processes of BC), the CMAQ model assumes all aerosol species in each of the Aitken, accumulation, and coarse modes are internally mixed and the accumulation-mode aerosols (including BC) are hydrophilic [Byun and Ching, 1999;Binkowski and Roselle, 2003].…”
Section: Model Simulationsmentioning
confidence: 99%
“…In atmospheric physics, this problem is known as "inertial impaction" and is relevant for estimating rates in rain formation or wet deposition of aerosols where a falling water drop scavenges smaller cloud droplets or solid pollutants. Studies of such problems often rely on collision efficiencies and, again, mainly formulas from laminar flow conditions are used (Berthet et al 2010). A popular formula is that of Slinn (1974), who proposed a fit of the collision efficiency for the inertial impaction regime.…”
Section: Introductionmentioning
confidence: 99%